Penerapan Inkubator Penetas Telur Ayam Secara Otomatis Berbasis Internet Of Things (Iot) Dalam Upaya Peningkatan Usaha Peternakan Ayam Di Desa Oelbubuk, Kecamatan Molo Tengah, Kabupaten Timor Tengah Selatan - Bale, Jefri; Tarigan, Ben; Selan, Rima; Modok, Renold (Universitas Pahlawan Tuanku Tambusai, 2023)
The Community Service Program through community partnerships is implemented to support national programs in improving the community's economy and efforts to prevent stunting and by increasing chicken farming businesses through the use of egg hatching incubator. Mitra is a community consisting of 20 (twenty) people and is part of the